2016
DOI: 10.22260/isarc2016/0112
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Migrating from Desktop-Based BIM in Construction

Abstract: -Recent studies increasingly offer new Building Information Modelling (BIM) solutions and some other studies are modelling BIM adoption and implementation practices. However, the migrating process from the current practice of using desktopbased BIM to a web-based BIM covering broader activities of the entire project lifecycle is complicated. This paper intends to develop the migrating process including main factors that inhibit higher level of web-based BIM usage (e.g. digital autonomous online systems) at con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In recent practices, the application of AI for generative design along with BIM is discussed by [46], as well as IoT and photogrammetry [46]. The shift from desktop-based BIM to web-based BIM also provided more flexibility and opportunity for BIM usage in OSC supply chain management [88]. In summary, three research gaps can be summarized from these reviews:…”
Section: End-of-life: Minimize Construction and Demolitionmentioning
confidence: 99%
“…In recent practices, the application of AI for generative design along with BIM is discussed by [46], as well as IoT and photogrammetry [46]. The shift from desktop-based BIM to web-based BIM also provided more flexibility and opportunity for BIM usage in OSC supply chain management [88]. In summary, three research gaps can be summarized from these reviews:…”
Section: End-of-life: Minimize Construction and Demolitionmentioning
confidence: 99%
“…Our experimentation revealed that a combination of algorithms can help to provide fairly accurate information about the quality of panels during construction. Our experimentation also assists draftsmen for as-built modelling and updating Building Information Modeling [69][70][71], based on the final panel layout and joint sizes. The construction industry has been known to be laggard in adopting new technologies, and there is a large effort to facilitate the process of technology adoption by exploring new applications and addressing barriers of technology implementation [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…While there is some attempt to identify the barriers of technology adoption, the construction industry continues to lag in utilizing new technologies, and is generally adverse to change as discussed by Nicolini [22]; Bowden et al [2]; Nikas et al [23]; Harty [24]; Sepasgozar et al [25], Milliou and Petrakis [26]. The Melbourne Institute of Applied Economics and Social Research [27] [29] wondered why only a small portion of the photovoltaic modules was adopted by builders in construction market so far, when the photovoltaic application has a strong market in overall.…”
Section: Terms and Conceptsmentioning
confidence: 99%